Effectiveness of Community Language Learning Method on English Grammar: A Study of JNV Papumpare of Arunachal Pradesh - Singh, Vivek; Pertin, Cheenang (THE PRIMARY TEACHER, 2022)
Language learning has always been an important sign of child development. Learning a first language happens naturally in sync with a child’s growth and development, and the learning of a second language becomes challenging, especially if it’s a language as distant as from the first language. Community Language Learning (CLL) is a method that attempts to remove the challenging aspects of learning a language. The present paper examines the effectiveness of CLL with respect to English language learning as opposed to the traditional methods practiced in Indian classrooms, and also its impact on the attitude of the learners towards the language learning.